2004
DOI: 10.2337/diacare.27.5.1148
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity in the Offspring of Women With Type 1 and Type 2 Diabetes

Abstract: OBJECTIVE -To determine if insulin sensitivity is altered in prepubertal offspring exposed to a diabetic intrauterine environment.RESEARCH DESIGN AND METHODS -Fifteen control children, 17 offspring of type 1 diabetic women, and 10 offspring of type 2 diabetic women, aged between 5 and 10 years, underwent a frequently sampled intravenous glucose tolerance test (FSIGTT). Weight and height were measured, and body composition was calculated using bioelectrical impedance. Bergman's minimal model was applied to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 23 publications
(23 reference statements)
5
40
0
1
Order By: Relevance
“…Given the mean age at diagnosis of diabetes in these women (12 years) and the fact that the majority were treated with insulin, we can assume that most of these women had type 1 diabetes. Studies to date that have examined the association of existing maternal type 1 diabetes with future offspring BMI or other markers of adiposity have produced varied results, with some showing greater BMI/adiposity in offspring of such mothers [30,33] and others, like ours, showing no association [34,35]. This variation could be due to small sample sizes in all of these studies, the number of mothers with existing diabetes in each study being 17 [35], 26 (our study), 61 [34], 75 [33] and 160 [30].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Given the mean age at diagnosis of diabetes in these women (12 years) and the fact that the majority were treated with insulin, we can assume that most of these women had type 1 diabetes. Studies to date that have examined the association of existing maternal type 1 diabetes with future offspring BMI or other markers of adiposity have produced varied results, with some showing greater BMI/adiposity in offspring of such mothers [30,33] and others, like ours, showing no association [34,35]. This variation could be due to small sample sizes in all of these studies, the number of mothers with existing diabetes in each study being 17 [35], 26 (our study), 61 [34], 75 [33] and 160 [30].…”
Section: Discussionmentioning
confidence: 56%
“…Studies to date that have examined the association of existing maternal type 1 diabetes with future offspring BMI or other markers of adiposity have produced varied results, with some showing greater BMI/adiposity in offspring of such mothers [30,33] and others, like ours, showing no association [34,35]. This variation could be due to small sample sizes in all of these studies, the number of mothers with existing diabetes in each study being 17 [35], 26 (our study), 61 [34], 75 [33] and 160 [30]. In addition to these studies, a recent study demonstrated that the adult offspring of mothers with existing type 1 diabetes during their pregnancy (n=15) had similar mean BMI, waist/hip ratio and total fat mass to offspring whose fathers had type 1 diabetes (n=15) [36].…”
Section: Discussionmentioning
confidence: 56%
“…Two additional studies were identified through a search of forward citations [15,48] and four [49][50][51][52] from hand-searching the reference lists of included papers, giving 34 papers in total. Five cohorts were reported in more than one paper, so only the study that reported the outcomes at an age closest to the overall median age of all studies (7 years) was included in the meta-analysis; 10 papers were excluded on this basis [25, 35, 36, 38-40, 42, 47-49].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to a prior study by Plagemann et al (7), in our GDM offspring cohort, low birth weight was not associated with childhood obesity. The focus of most studies of diabetic pregnancies has been on preexisting type 1 or type 2 diabetes (4,6,18,19), or populations with preexisting and gestational diabetes were combined (20,21,4). Here, we explicitly excluded women with preexisting diabetes because diabetic vascular disorders may cause placental dysfunction and intrauterine growth retardation.…”
Section: Birth Weight and Childhood Overweightmentioning
confidence: 99%